The Literary Mind of Medieval and Renaissance Spain - Green, Otis H. (Otis Howard), 1898-1978 (Book collections on Project MUSE., 1970)
The twelve essays in this fiorilegio of the work of Otis H. Green afford a representative view of the thought and scholarship of one of the world's foremost Hispanists. In each of them is developed some important facet of the intellectual milieu of the Middle Ages and Renaissance, reflecting Otis Green's life-long and wide-ranging quest for evidence that would broaden our understanding of those complex periods and correct the misapprehensions which have gathered about them. Included are important sections of his great work, Spain and the Western Tradition and essays from journals now difficu.